El contrato de outsourcing : algunas reflexiones prácticas - Santos Martins, Luis dos (IE Cátedra José María Cervelló, 2013)
There is a lack in analysing Third Sector from a philosophical perspective. It is very complicated to answer many questions that are arising: Why men are concerned to the problems other men are involved in? Which is thedriving force of the Social Sector? Why are NGOs legitimated to supportsocial matters? What have NGOs to do in the XIX century? This questions need to be answered to fix correctly future strategy, mission and objectives. It is necessary to build an ethical-political frame to understand deeply how Third Sector works. This paper studies from a philosophicalapproach the relationship between NGO and beneficiary, the changeshappened in the XX century and the challenges NGO need to face in theforthcoming years.
The outsourcing agreement: some practical insights
Keywords: Tercer Sector; ONG; Enfoque ético-político; Relación; Libertad; Justicia; Third Sector; NGOs; Ethical-political focus; Relationship; Liberty; Justice; 72 Filosofía; ODS 16 - Paz, justicia e instituciones sólidas